Effect of Payments for Disease Specific Care on Poverty Estimates in Nepal - Adhikari, Shiva Raj (Economic Journal of Development Issues, 2018)
The popular poverty estimation method follows the cost of basic needs approach through estimation of poverty line. Health care is a basic necessity of life, as important as food, shelter, and clothing; however, current practice of estimating poverty indicators in Nepal does not capture the basic health care cost. Not accounted of out of pocket payment for health care into the poverty estimation could give a misleading picture of trends in poverty over time. Ignoring health care costs altogether can result in misclassifying which households or individuals are in the greatest need. Therefore, the paper estimated the revised poverty statistics with explicitly accounting for basic health care needs along with other basic needs such as food, clothing, and shelter by utilizing the Nepal living standard surveys(2010/11) data. The paper used the Foster, Greer and Thorbecke (FGT) poverty estimation method to estimate hidden or underestimated poverty before and after accounting health care payment. The results show that official poverty statistics are significantly underestimated while incorporating basic health care cost in the estimation of poverty statistics in Nepal. Out of pocket payments for health care of different diseases have different impoverishment impacts in terms of incidence and intensity of poverty. Higher average costs of health care cause higher impoverishment impacts. This paper indicates that incidence of poverty is underestimated by almost 4 percentage point and intensity of poverty is underestimated by 0.29 percent based on official estimation of poverty. Economic Journal of Development Issues Vol. 23 & 24 No. 1-2 (2017) Combined Issue, Page : 18-34